Acid-activated chitosan-modified Iranian bentonite for adsorption of Cu(II) and Zn(II) from water; A green and sustainable water treatment approach - Sam Daftari; Mojgan Salavati; Manoochehr Mortazavi Chamchali (PLoS ONE, 2026)
This study evaluates the adsorption performance of an Iranian bentonite modified through two routes: activation with HNO 3 followed by calcination at 500 °C yielding NWF adsorbent and activation with HCl followed by chitosan intercalation to obtain HWF adsorbent. Batch experiments assessed Cu 2+ and Zn 2+ removal from aqueous solutions under varying pH, contact time (5–45 min), sorbent dosage (10–150 mg), initial concentration (20–200 mg/L), and temperatures (20–45°C). Atomic Absorption Spectroscopy was used to evaluate heavy metal concentrations. Nonlinear isotherm fitting showed that the Langmuir model described the data well with high mass normalized capacities under the low-dose condition. Freundlich fits indicated favorable adsorption on heterogeneous surfaces. Kinetics followed the pseudo-second-order model (R² = 0.996–0.998), could be described by chemisorption and in case of NWF, faster uptake (higher k 2 ) achieved. Optimal adsorption performance occurred at a pH of approximately 6–7, achieving equilibrium capacities ( q e ) as high as 99.0 mg/g and blank tests at pH ≥ 8 minimized contributions from metal hydroxide precipitation. Thermodynamic analysis has been carried out to confirm spontaneous and endothermic adsorption in temptatures ranged from 20–45°C. X-ray Diffraction, Fourier Transform Infrared Spectroscopy and Scanning Electron Microscopy corroborated successful modification and enhanced site accessibility. The results of this study showed that acid-activated and chitosan-modified bentonites are low-cost, effective, and sustainable sorbents for Cu 2+ and Zn 2+ removal from water, with practical relevance to wastewater treatment.